First detection and genomic analysis of mcr-1-positive Salmonella Infantis isolated from a broiler production system in the United Arab Emirates - Habib, Ihab; Mohamed, Mohamed-Yousif Ibrahim; Lakshmi, Glindya Bhagya; Al Marzooqi, Hassan Mohamed; Afifi, Hanan Sobhy; Shehata, Mohamed Gamal; Elbediwi, Mohammed (Frontiers in Veterinary Science, 2025)
This study reports the first detection of mcr-1.1-mediated colistin resistance in Salmonella enterica serovar Infantis from a commercial broiler farm in the United Arab Emirates (UAE). Two S. infantis isolates (SAL_93 and SAL_94) were recovered from caecal droppings and characterized using whole-genome sequencing (WGS). Genomic analysis revealed a single-nucleotide polymorphism (SNP) difference between them, confirming their close epidemiological relationship. Both isolates belonged to multilocus sequence type 32 and exhibited multidrug resistance (MDR), including resistance to colistin (MIC = 4 mg/L) and ciprofloxacin (MIC = 0.5 mg/L). Notably, the mcr-1.1 gene was detected on a conjugative IncX4 plasmid. Additionally, the isolates harbored a large (275,043 bp) conjugative IncFIB plasmid carrying multiple AMR genes, including aadA1, sul1, tet(A), qacEdelta1. Bioinformatic analysis showed a high identity for globally reported mcr-1.1-carrying IncX4 plasmids. The investigation of virulence-associated factors in the studied isolates identified 162 potential virulence-related genes. These included genes linked to the type 3 secretion system, specifically those encoded by pathogenicity island-1 (SPI-1). However, multiple genes linked to the second type 3 secretion system, encoded by SPI-2, were absent in all isolates. These findings suggest a potential risk of horizontal gene transfer in poultry production. Given these risks, the UAE’s recent ban on colistin in veterinary medicine marks a crucial step in mitigating AMR transmission within a One Health framework.